Integrated Remediation Processes Toward Heavy Metal Removal/Recovery From Various Environments-A Review - Selvi, Adikesavan; Rajasekar, Aruliah; Theerthagiri, Jayaraman; Ananthaselvam, Azhagesan; Sathishkumar, Kuppusamy; Madhavan, Jagannathan; Rahman, Pattanathu K. S. M. (Frontiers in Environmental Science, 2019)
Addressing heavy metal pollution isone of the hot areas of environmental research.Despite natural existence, various anthropomorphic sources have contributed to an unusually high concentration of heavy metals in the environment.They are characterized by their long persistence in natural environment leading to serious health consequences in humans, animals, and plants even at very low concentrations (1 or 2 μg in some cases). Failure of strict regulations by government authorities is also to be blamed for heavy metal pollution. Several individual treatments, namely, physical, chemical and biological are being implied to remove heavy metals from the environment.But, they all face challenges in terms of expensiveness and in-situ treatment failure.Hence, integrated processes are gaining popularity as it is reported to achieve the goal effectively in various environmental matrices and will overcome a major drawback of large scale implementation.Integrated processes are the combination of two different methods to achieve a synergistic and an effective effort to remove heavy metals. Most of the review articles published so far mainly focus on individual methods on specific heavy metal removal, that too from a particular environmental matrix only.To the best of our knowledge, this is the first review of this kind that summarizes on various integrated processes for heavy metal removal from all environmental matrices. In addition, we too have discussed on the advantages and disadvantages of each integrated process, with a special mention of the few methods that needs more research attention. To conclude, integrated processes areproved as a right remedial option which has been detaily discussed in the present review. However, more research focus on the process is needed to challenge the in-situ operative conditions. We believe, this review on integrated processes will surely evoke a research thrust that could give rise to novel remediation projects for research community in the future.